A simple method to quickly and simultaneously purify and enrich intact rat brain microcapillaries and endothelial and glial cells for ex vivo studies and cell culture - Lenhard, Thorsten; Hülsermann, Uta; Martinez Torres, Francisco Javier; Fricker, Gert; Meyding-Lamadé, Uta (Brain research, 2013)
The blood-brain barrier is morphologically composed of cerebral microcapillary endothelium through its tight junctions. It serves as a mechanical, metabolic and cellular barrier and can also protect the brain from pathogen invasion. Many brain diseases involve a disturbance of blood-brain barrier function either as a consequence of a noxa or as primary failure. In vitro models of the blood-brain barrier are suitable tools to study drug transport, pathogen transmigration and leukocyte diapedesis across the cerebral endothelium. Such models have previously been derived mainly from porcine or bovine brain tissues. We describe here a simple method by which rat cerebral microcapillaries and cells of glial origin can be quickly and simultaneously purified. By using a capillary fragment size restriction method based on glass bead columns different fractions can be separated: vital, long capillary fragments for ex vivo uptake studies and smaller capillary fragments for endothelial culture. Furthermore, fractions can be obtained for astroglial and oligodendroglial cell cultures. With this method both microcapillary enrichment and glial cell purification are quickly achieved, which reduces expenditure, number of required animals and laboratory working time.
Gesehen am 19.01.2022